Cofinitely Lifting Semi modules (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this paper (cofinitely lifting semimodules) are defined which generalize cofinitely lifting modules. We looking for some properties of these semimodules. We demonstrate all cofinite direct summnd of (cofinitely lifting semimodule) is ("cofinitely lifting").